Competitive advantage in global markets: the case of the salmon industry in Chile. Issue 6 (7th October 2014) - Felzensztein, Christian; Gimmon, Eli
Abstract : Purpose: – This study aims to focus on how companies operating in international food commodity markets can improve their long-term competitiveness and profitability upon financial pressure. Management can choose between generic strategies of either cost leadership or enhanced value adding by differentiation and innovative marketing strategies. The aim of the paper is to highlight key findings from a case study perspective. Design/methodology/approach: – The research is set within the farmed salmon sector in the world's second largest producing country, Chile, which is also a fast growing emerging economy in Latin America. Semi-structured personal interviews were conducted with General Managers of this global industry. Findings: – Unexpectedly, our findings show that executives preferred competitive strategy of cost reduction rather than differentiation. Based on previous research, we recommend managers of individual firms and trade associations to play down commoditisation and to pursue differentiation strategies with particular attention to emergent environmental attributes. Originality/value: – Practitioners from Latin America may learn on empirical considerations of international marketing strategies taking this competitive global industry as an example. An overall cost leadership strategy is not sufficient in a mature industry, and customer-oriented strategies are needed more than production-oriented strategies. Clustered firms are recommended to benefit from differentiation strategies with particular attention to emergent environmental attributes.